Decoding NY-ESO-1 TCR T cells: transcriptomic insights reveal dual mechanisms of tumor targeting in a melanoma murine xenograft model - Alsalloum, Alaa; Alrhmoun, Saleh; Perik-Zavosdkaia, Olga; Fisher, Marina; Volynets, Marina; Lopatnikova, Julia; Perik-Zavodskii, Roman; Shevchenko, Julia; Philippova, Julia; Solovieva, Olga; Zavjalov, Evgenii; Kurilin, Vasily; et al. (Frontiers in Immunology, 2024)
The development of T cell receptor-engineered T cells (TCR-T) targeting intracellular antigens is a promising strategy for treating solid tumors; however, the mechanisms underlying their effectiveness remain poorly understood. In this study, we employed advanced techniques to investigate the functional state of T cells engineered with retroviral vectors to express a TCR specific for the NY-ESO-1 157-165 peptide in the HLA-A*02:01 context. Flow cytometry revealed a predominance of naïve T cells. Gene expression profiling using NanoString technology revealed upregulation of genes encoding chemokine receptors CCR2 and CCR5, indicating enhanced migration towards tumor sites. In the SK-Mel-37 xenograft model, these transduced T cells achieved complete tumor eradication. Furthermore, single-cell RNA sequencing (scRNA-seq) conducted 14 days post-TCR T cell infusion provided a comprehensive analysis of the in vivo adaptation of these cells, identifying a distinct subset of CD8+ effector T cells with an NK cell-like gene expression profile. Our findings indicate that NY-ESO-1 TCR-transduced T cells have the potential to mediate dual antitumor effects through both antigen-independent NK-like and antigen-specific CTL-like responses. This study underscores the potential of NY-ESO-1 TCR-T cells as potent tumor-eradicating agents, highlighting the importance of harnessing their versatile functional capabilities to refine and enhance therapeutic strategies.